Interaction-centred design: an end user evaluation of road intersection concepts developed using the cognitive work analysis design toolkit (CWA-DT). Issue 10 (2nd October 2020) - Read, Gemma J. M.; Salmon, Paul M.; Goode, Natassia; van Mulken, Michelle; Lenné, Michael G.; Stevens, Nicholas; Walker, Guy H.
Abstract: Crashes at intersections represent an important road safety problem. Interactions between different road user types, such as between vehicles and vulnerable road users, are a particular concern. It has been suggested driver-centric road design plays a role in crashes. A multi-road user evaluation of three novel intersection designs is described. The designs were generated using the Cognitive Work Analysis Design Toolkit, underpinned by sociotechnical systems theory. The desktop evaluation involved drivers, motorcyclists, cyclists and pedestrians rating the design concepts against alignment with design goals, sociotechnical systems theory and usability, and providing feedback on the positive and negative aspects. Two concepts received more positive ratings and feedback in comparison to a concept that provided more user autonomy. The evaluation results also highlight clear differences in needs across road user groups. The design and evaluation process demonstrates how sociotechnical systems values and principles can be applied in the design of public spaces. Practitioner Summary: This study involved a participatory evaluation of novel road intersection designs, based on sociotechnical systems theory. The results identified important differences in needs and preferences across road user groups and demonstrate the value of sociotechnical systems theory and user participation in road transport design and evaluation processes. Abbreviations: CWA-DT: cognitive work analysis design toolkit; WDA: work domain analysis; SUS: system usability scale